THE LEVEL OF MOTOR SKILLS DEVELOPMENT COMPARED TO THE REQUIREMENTS OF THE NATIONAL EVALUATION SYSTEM IN GRADE 4 STUDENTS - Marina IORDĂCHESCU; Carmen Mariana GEORGESCU; Dorina ORȚĂNESCU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2021)
A good knowledge of the level of development of motor skills of students allows us to identify/improve/establish the level ofmanifestation of its components and the relationships between them. Physical fitness is a strong indicator of health in childhood and adolescence and a main objective for the specialist in the field. In this context, the present study was carried out in 2018-2019and aimed to determine the level of development of motor skills in fourth-grade students from several school units in Craiova, compared tothe requirements of the national evaluation system. Materials and methods.In order to ascertain the level of somatic and motor development of the group included in the present approach, anthropometric measurements and motor testswere applied, namely: height, weight, torso/chest height, abdominal perimeter, arm span,thestanding long jump, supine trunk lifts, the 25mrunning speedand the long-distancerunning. The recording methods applied were those already standardized. Results. Following the analysis of the recorded data we can state that,as far as somatic indicators are concerned, the investigated group presents values below the average of students of the same age in both girls and boys, and there are no significant differences between sexes. However, there is a downward trend inthe average values in the motor tests, many of the recorded values being above therequirements of the national evaluation system. Also, the body mass index calculated for the target group has values that place the studentsin a comfortable range, the average being below the underweight threshold. Conclusions. We consider such approaches very useful, both for a diagnosis of what is actually happening in the school, and forapplying targeted intervention programs to improve any deficiencies